Pesticide Utilisation, Regulation and Future Prospects in Small Scale Horticultural Crop Production Systems in a Developing Country - Karungi, J.; Kyamanywa, S.; Adipala, E.; Erbaugh, M. (IntechOpen, 2011)
None